Mastering Writing at Greater Depth A guide for primary teaching - Bushnell, Adam; Bushnell, Adam; Gill, Angela; Waugh, David (SAGE Publications, 2020)
How do teachers identify the potential for greater depth writing and encourage children to meet their full potential? This book was created by people who are not only passionate about primary education, but who are also leading experts in their own particular areas. They have made use of their wide experience to offer practical guidance on greater depth writing, while underpinning this with theoretical understanding. We hope that reading this book helps you to reflect on what greater depth writing looks like and how you can encourage children to write at greater depth. You will find many suggestions for teaching lessons that encourage children to write at greater depth underpinned by theory.